2013
DOI: 10.1089/jop.2012.0115
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ocular Hypotensive Medication Types with Dynamic Contour Tonometry and Goldmann Applanation Tonometry Measurements in a Glaucoma and Ocular Hypertensive Population

Abstract: The difference between DCT and GAT IOP measurements is found to be statistically significantly higher in patients receiving CAIs either as monotherapy or as a part of a combined ocular hypotensive treatment, while DCT and GAT readings remain unaffected. The type of diagnosis and the number of ocular hypotensive medications had no statistically significant influence on ΔIOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, in glaucomatous eye(s), this correlation is variable. Although it is widely known that IOP measurement using DCT is not significantly influenced by CCT compared with GAT, previous studies have reported that both GAT and DCT measurement values demonstrate significant correlation with CCT [ 21 , 22 ] or non-significant correlation with CCT in glaucomatous eyes [ 23 , 24 ]. CC is also affected by IOP measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…However, in glaucomatous eye(s), this correlation is variable. Although it is widely known that IOP measurement using DCT is not significantly influenced by CCT compared with GAT, previous studies have reported that both GAT and DCT measurement values demonstrate significant correlation with CCT [ 21 , 22 ] or non-significant correlation with CCT in glaucomatous eyes [ 23 , 24 ]. CC is also affected by IOP measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of topical CAIs either as monotherapy or in combination with other IOP-lowering medications resulted in a significantly greater difference in IOP measured by dynamic contour tonometry (DCT) and Goldmann applanation tonometry (GAT). The diagnosis type (OAG or OHT) and the number of IOP-lowering medications had no significant influence on the difference in IOP as measured using the two instruments [13]. Dorzolamide/timolol and brinzolamide/timolol FCs effectively decreased IOP, which was a lower target IOP with dorzolamide/timolol than with brinzolamide/timolol, in patients with primary OAG or normal tension glaucoma [44].…”
Section: Resultsmentioning
confidence: 88%
“…In comparison, a triple PF tafluprost with PF dorzolamide/timolol FC resulted in a significant improvement in 24-hour IOP control as compared to the latanoprost baseline treatment [38]. Administration of CAIs either as monotherapy or in combination with other IOP-lowering medications resulted in a statistically significant difference in IOP measured by DCT and GAT [13].…”
Section: Carbonic Anhydrase Inhibitorsmentioning
confidence: 89%
See 1 more Smart Citation